Developments in medical education in response to the COVID-19 pandemic: A rapid BEME systematic review: BEME Guide No. 63. (1st November 2020) - Gordon, Morris; Patricio, Madalena; Horne, Laura; Muston, Alexandra; Alston, Sebastian R.; Pammi, Mohan; Thammasitboon, Satid; Park, Sophie; Pawlikowska, Teresa; Rees, Eliot L.; Doyle, Andrea Jane; Daniel, Michelle
Abstract: Background: The novel coronavirus disease (COVID-19) was declared a pandemic in March 2020. This rapid systematic review synthesised published reports of medical educational developments in response to the pandemic, considering descriptions of interventions, evaluation data and lessons learned. Methods: The authors systematically searched four online databases and hand searched MedEdPublish up to 24 May 2020. Two authors independently screened titles, abstracts and full texts, performed data extraction and assessed risk of bias for included articles. Discrepancies were resolved by a third author. A descriptive synthesis and outcomes were reported. Results: Forty-nine articles were included. The majority were from North America, Asia and Europe. Sixteen studies described Kirkpatrick's outcomes, with one study describing levels 1–3. A few papers were of exceptional quality, though the risk of bias framework generally revealed capricious reporting of underpinning theory, resources, setting, educational methods, and content. Key developments were pivoting educational delivery from classroom-based learning to virtual spaces, replacing clinical placement based learning with alternate approaches, and supporting direct patient contact with mitigated risk. Training for treating patients with COVID-19, service reconfiguration, assessment, well-being, faculty development, and admissions were all addressed, with the latter categories receiving the least attention. Conclusions: This review highlights several areas of educational response in the immediate aftermath of the COVID-19 pandemic and identifies a few articles of exceptional quality that can serve as models for future developments and educational reporting. There was often a lack of practical detail to support the educational community in enactment of novel interventions, as well as limited evaluation data. However, the range of options deployed offers much guidance for the medical education community moving forward and there was an indication that outcome data and greater detail will be reported in the future.